THE FIRST YEARS OF UZBEKISTAN’S INDEPENDENCE IN THE EYES OF THE TURKISH PRESS (TAMADDUN NURI JURNALI, 2025)
This article analyzes how the Republic of Uzbekistan was reflected in the Turkish media after it gained independence in 1991. It studies how the political, economic and cultural life of Uzbekistan was covered by the Turkish press in the early years, and how the flow of information was formed against the background of historical and cultural proximity between the countries.